Synthesis and Performance of Polycarboxylate Superplasticizer Based on a Novel Redox System of Manganese Dioxide/Acid - Siyong CHENG; Xintang WANG; Si WU; Luyan WANG (Medžiagotyra)
This study aims to develop a novel redox system based on manganese dioxide (MnO₂)/acid for synthesizing polycarboxylate superplasticizers (MPCE) via solution copolymerization of acrylic acid (AA) and methallyl polyoxyethylene ethers (TPEG). The performance of MPCE synthesized using MnO₂ combined with different acids (citric acid, tartaric acid, oxalic acid) was compared with two conventional redox systems: ascorbic acid (VC)/H₂O₂ and ammonium persulfate. The MnO₂/citric acid system proved most effective, attributed to its one-step reaction to generate primary free radicals. Optimal reaction conditions were determined as a molar ratio of AA to TPEG (Mn=2400) of 3.5:1.0 and [MnO₂]:[citric acid] of 1:1. The longer side chains of MPCE enhanced adsorption on cement particles and dispersing performance via steric hindrance. Cement paste containing MPCE-2400 showed superior dispersing ability, retention capacity, clay resistance, and hardened mechanical properties. The findings highlight the critical role of the MnO₂/acid redox system in optimizing MPCE synthesis.